Right middle lobe syndrome in a 7-year-old child - Ahmed Abdelaziz; Mostafa Kotb; Amal Sabry; Ahmed Daoud; Islam Elgamal; Khalid Karara; Abdelmeguid Ramadan; Waheed Etman (Elsevier, 2020)
Middle lobe syndrome (MLS) is defined as recurrent or chronic collapse of the middle lobe of the right lung. Although it was first described in 1984 by Graham et al., yet there are limited reviews on MLS especially in children as a result of vast etiologies, wide spectrum of presentation and lack of a consistent clinical definition. Herein, we present a case of MLS in a 7-year-old child who was presented after suffering from repeated chest infections for more than 3 years. Keywords: Atelectasis, Lingual syndrome, Middle lobe syndrome